Voices of Indonesian EFL Learners on Synchronous Learning amidst COVID-19 Pandemic - Maman Asrobi; Siti Ayu Surayya; Ari Prasetyaningrum (UIN Salatiga, 2021)
To ensure that the learning process during the COVID-19 pandemic runs smoothly, all universities in Indonesia have implemented online learning. However, based on the observations made, online learning, especially when carried out synchronously, appears to still be not as optimal as offline learning. This study aims to find out the voices of Indonesian EFL learners on synchronous learning during the covid-19 pandemic. Designed as descriptive qualitative, this study examined 50 students who voluntarily participated as the sampled group. In collecting the data, the researchers used a self-written reflection and questionnaire with four scales that were distributed using Google Form to the participants. The questionnaire was related to respectful attitude, benefits, and obstacles of synchronous learning. All collected data were then analyzed using the sequential explanatory processes. The result of data analysis revealed that Indonesian EFL learners still showed a good respectful attitude during the synchronous learning process, although they agreed that learning synchronously faces a few obstacles, such as unsupported devices and unfavorable learning environments. In addition, they also feel that the teaching and learning process synchronously during the COVID-19 pandemic provided them with several benefits, especially those related to safety, efficiency, and effectiveness.Keywords: EFL learners; synchronous learning; COVID-19 pandemic